Teaching writing by local culture contextual-based Approach - Hasman Hasman; Ilham Ilham; Amaluddin Amaluddin; Rafi'ah Nur (Universitas Muhammadiyah Enrekang, 2024)
Writing is one of communicative act that it is a process of expressing ideas, opinions, and ideas. It will be produced in some sequences of sentence by using graphic symbols. Writing process is more complex than this of course, and the various stages of drafting, reviewing, redrafting and writing. The method that the researcher employed in this research was quasi-experimental design. The data were analyzed by using quantitative approach. Apply two groups pre-test, post-test, namely experimental and control groups. The objective of the research is to find out whether or not the use of local culture contextual -based approach can improve the writing ability to the Second Semester Students of English Education Department of Muhammadiyah University of Parepare. It was proved by the difference between pretest and posttest result in experimental and control class. While, the result of the t-test in posttest was 3.380 and the t-table was 2.024. It showed that t-test value was greater than t-table value. Learning through a local culture-based approach is able to improve students' writing skills because based on the data found, students seem interested in the learning being carried out. several influencing factors are: (1) students feel this learning is very close to them because it raises the culture around them. (2) The involvement of students is increased considering that the presentation of text learning presented in learning is very closely related to local events, environment, norms and culture. (3) Students understand important themes and issues that are connected to their own knowledge and experiences.